Analisis Kinerja Keuangan Pada PT Indo Tambang Raya Megah TBK Yang Terdaftar di Bursa Efek Indonesia (BEI) Priode 2018-2022 - Delva Handayani; Hendry Saladin; E. Erdiansyah (Universitas Warmadewa, 2024)
Study this aim for know level performance finance at PT Indo Tambangraya Majestic Tbk winch is listed on the Indonesia stock exchange for the 2018-2022 period. Methid used in study this is method descriptive with approach qualitative. Population study this is report finance at PT Indo Tambangraya majestic Tbk which is listed on the Indonesia stock exchange. Technique taking sample is report position finance and report profit make a loss on 2018-2022. Technique data analysis on study this that is with method count ratio finance use tool measuring ratio liquidity (Current Ratio and Cash Ratio), ratio solvency (DAR and DER), ratio activity (TATO), and ratio profitability (ROI and ROE). Based on results calculation of research avarages ratio finance at PT Indo Tambangraya Majestic Tbk on 2018-2022, ratio liquidity showing level performance finance current ratio by 239% with standard the industry is 200% meaningful company in circumstance good and cash ratio by 141% whit standart the industry is 50% meaning company in circumstance good. Ratio solvancy showing that DAR value is 28% with standard the industry is 35% meaning company in circumstances good and DER is 39% whit standard the industry is 90% meaning company this in circumstances good. Ratio activity showing that TATO value is 128% with standard the industry is 2 times or 200% meaning company this considered not enough good. Ratio profitability showing that ROI value of 20% with standard the industry is 30% meaning company thus in circumstances not enough well, ROE is 29% with standard the industry is 40% meaning company in circumstances not enough good.